Hubungan Komunikasi Terapeutik Perawat terhadap Penurunan Tingkat Kecemasan Pasien Pra Vaksinasi Meningitis di Rumah Sakit Umum Daerah Pambalah Batung Amuntai - Radaina, Jannatul; Indari Indari (Lembaga Pengembangan Kinerja Dosen, 2026)
Meningitis is a serious infectious disease that can be prevented through vaccination; however, the vaccination process often causes anxiety in patients, especially during the pre-procedure phase. Uncontrolled anxiety can affect patient readiness and comfort. Therapeutic communication by nurses is one intervention that has the potential to reduce this level of anxiety. This study aims to determine the relationship between nurses’ therapeutic communication and the anxiety levels of patients prior to meningitis vaccination at Pambalah Batung Amuntai Regional General Hospital. This study used a quantitative analytic design with a cross-sectional approach. The sample consisted of 107 respondents selected using a convenience sampling technique. Data on therapeutic communication were collected using an observation sheet, while anxiety levels were measured using the DASS questionnaire (anxiety subscale). Data analysis was conducted using univariate and bivariate methods with the Chi-Square test at a significance level of 0.05. The results showed that most therapeutic communication was in the good category, and patient anxiety levels were predominantly in the normal category. Statistical test results indicated a significant relationship between nurses’ therapeutic communication and patient anxiety levels (p = 0.000 < 0.05). The better the therapeutic communication provided, the lower the patient’s anxiety level. In conclusion, nurses’ therapeutic communication plays an important role in reducing patient anxiety prior to meningitis vaccination and needs to be optimized in nursing practice.